STOCHASTIC MODEL UPDATING BASED ON THE KRIGING MODEL AND WAVELET PACKET ENERGY SPECTRUM (MT) - SUN YongPeng; PENG ZhenRui; BAI Yu (Jixie qiangdu)
Aiming at the low accuracy and efficiency of stochastic model updating, a stochastic finite element model updating method based on the Kriging model and wavelet packet energy spectrum was proposed. Firstly, assume that the parameters and response characteristics of the model to be updated obey normal distributions, the uncertainty model updating was transformed into the updating of mean and standard deviation. Secondly, the parameters to be updated were taken as inputs of Kriging model, the node energies extracted by the acceleration frequency response function after wavelet packet decomposition were taken as the outputs, the political optimizer algorithm was introduced to optimize the correlation coefficient to construct Kriging model. Then, minimize the absolute value of the difference between the test response and the predicted response as the objective function for updating mean, and minimize the cross entropy as the objective function for updating standard deviation, and updated the parameters mean and standard deviation through the political optimizer algorithm. Finally, taking a space truss structure as the example, the elastic modulus and density were selected as the parameters to be updated to verify the feasibility of the proposed method. The results show that the proposed method can effectively update the mean and standard deviation of structural parameters, and errors of the updated mean and standard deviation are less than 0.1% and 3.5%, respectively.